The microbiota and metabolome dynamics and their interactions modulate solid-state fermentation process and enhance clean recycling of brewers’ spent grain - Xie, Yueqin; Liu, Dongyun; Liu, Yang; Tang, Jiayong; Zhao, Hua; Chen, Xiaoling; Tian, Gang; Liu, Guangmang; Cai, Jingyi; Jia, Gang (Frontiers in Microbiology, 2024)
The massive yield of brewers’ spent grain (BSG) waste inevitably threaten environmental health. Here, solid-state fermentation (SSF) technology featuring multi-strain (MS) inoculation and high-throughput sequencing technology were employed to facilitate the sustainable and clean recycling of BSG waste while revealing the associated underlying microbiological and metabolic mechanisms. MS inoculation displayed a lower pH value (3.91 vs. 4.12) and neutral detergent fiber content (446.24 vs. 476.23 g/kg DM), a higher levels of lactic acid (86.64 vs. 33.07 g/kg DM), acetic acid (6.13 vs. 4.87 g/kg DM), propionic acid (2.78 vs. 2.18 g/kg DM) and crude protein (307.5 vs. 289.15 g/kg DM) than those in the control group. Moreover, MS inoculation inhibited the formation of non-protein-N and ammonia-N, and spoilage microorganism resuscitation, while enhanced substrate preservation. Microbiologically, during the SSF, the group treated with MS inoculation exhibited an increase in the relative abundance of Leuconostoc (0.58%∼6.60%), Weissella (6.22%∼15.42%), Enterococcus (3.15%∼9.08%), Bacillus (17.63%∼31.29%), Lactobacillus (12.89%∼8.29%), Pseudoalteromonas (12.87%∼16.29%), and a decrease in the relative abundance of Acinetobacter (0.79%∼0.02%) and Enterobacteriaceae (0.78%∼0.24%). Metabolically, starch and sucrose metabolism, arginine and proline metabolism, and phenylalanine metabolism significantly influenced the quality of extruded BSG fermented by MS during SSF. The examination of the correlation between the microbiota, metabolites, and fermentation parameters revealed that complex interactions between microbes and the environment factors impact metabolite production. Collectively, inoculating with MS improved fermentation quality and stability, facilitated the clean recycling of BSG, which is linked to complex interactions among microbes, the environment factors and metabolite production.